Cyclic Polymer with Alternating Monomer Sequence. Issue 22 (21st August 2015) - Zhu, Wen; Li, Zi; Zhao, Youliang; Zhang, Ke
Abstract : Cyclic polymers with alternating monomer sequence are synthesized for the first time based on the ring‐closure strategy. Well‐defined telechelic alternating polymers are synthesized by reversible addition–fragmentation chain transfer polymerization by copolymerizing the electron acceptor monomer of N ‐benzylmaleimide and donor monomer of styrene with a feed ratio of 1 between them. The corresponding cyclic alternating polymers are then produced by the UV‐induced Diels–Alder click reaction to ring‐close the linear alternating polymer precursors under highly diluted reaction solution. Abstract : Cyclic polymers with alternating monomer sequences are synthesized for the first time by the ring‐closure strategy. In this approach, well‐defined telechelic alternating polymers are synthesized by reversible addition–fragmentation chain transfer polymerization through copolymerizing electron acceptor monomer of N ‐benzylmaleimide and donor monomer of styrene. The corresponding cyclic alternating polymers are then produced by the UV‐induced Diels–Alder click reaction to ring‐close the linear alternating polymer precursors.